Trends in Politeness Research in Indonesian Language Education Journals: A Decade of Insights (2013–2023) - Fuadin, Ahmad; Syihabuddin, Syihabuddin; Hidayat, Mupid; Mulyati, Yeti (FKIP Universitas Lampung, 2025)
Abstract: Trends in Politeness Research in Indonesian Language Education Journals: A Decade of Insights (2013–2023). Objective: Linguistic politeness is a crucial element in communication that reflects cultural norms and social values, particularly in multicultural societies like Indonesia. This study aims to analyze trends in politeness research within Indonesian language and literature education journals indexed in SINTA during 2013–2023. Methods: Employing a qualitative descriptive approach and the Systematic Literature Review (SLR) method, this research examines 63 articles based on publication volume, research methods, focus areas, theoretical adaptations, and practical implications. Articles were selected using the keywords